Effect on public health of a possible increase of the maximum level for 'aflatoxin total' from 4 to 10 μg/kg in peanuts and processed products thereof, intended for direct human consumption or use as an ingredient in foodstuffs. (8th February 2018) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hogstrand, Christer; et al.
Abstract: EFSA was asked to deliver a scientific opinion regarding the effect on public health of a possible increase of the maximum level (ML) for 'aflatoxin total' (AFT; sum of aflatoxin B1, aflatoxin B2, aflatoxin G1 and aflatoxin G2) from 4 to 10 μg/kg in peanuts and processed products thereof. Aflatoxins are genotoxic and cause hepatocellular carcinomas in humans. The Panel on Contaminants in the Food Chain (CONTAM Panel) evaluated 8, 085 samples of peanuts and 472 samples of peanut butter, with > 60% left‐censored. The mean concentration of AFT in peanuts was 2.65/3.56 μg/kg (lower bound (LB)/upper bound (UB)) with a maximum of 1, 429 μg/kg. The mean concentration in peanut butter was 1.47/1.92 μg/kg (LB/UB) with a maximum of 407 μg/kg. Peanut oil was not included since all data were left‐censored and the ML does not apply for oil. Exposure was calculated for a 'Current ML' and 'Increased ML' scenario, and mean chronic exposure estimates for consumers only, amounted to 0.04–2.74 ng/kg body weight (bw) per day and 0.07–4.28 ng/kg bw per day, respectively. The highest exposures were calculated for adolescents and other children. The CONTAM Panel used the cancer potencies estimated by the Joint FAO/WHO Expert Committee on Food Additives for the risk characterisation. Under the scenario of the current ML, the cancer risk was estimated to range between 0.001 and 0.213 aflatoxin‐induced cancers per 100, 000 person years. Under the scenario of the increased ML, it ranged between 0.001 and 0.333 aflatoxin‐induced cancers per 100, 000 person years. Comparing these data calculated under the current ML scenario with the yearly excess cancer risk of 0.014 shows a higher risk for consumers of peanuts and peanut butter in some surveys. The calculated cancer risks indicate that an increase of the ML would further increase the risk by a factor of 1.6–1.8.